Effects of curing methods on the flexural strength of composites - Rodriguez, Irene Maye D
The purpose of this study were to determine and compare the flexural strength of composites and the effects of three curing methods on this property. f-"our brands of composites namely: Clearfil AP-X (Kuraray), a direct, universal-use composites; Beautifil (Shofu), a direct, universal-use composites; Filtek P-60 (3M), a direct/indirect, posterior composites; and Solidex (Shofu), an indirect universal-use composite, were subjected to different curing methods. Six specimens fro each brand were subjected to light curing, light curing followed by multi-focal light oven curing for five minutes and light curing followed by immersion in boiling water for ten minutes. Flexural strengths were determined using a Universal Testing Machine at a constant rate of 0.5 mm/minute. Data were analyzed by two-way ANOVA and Duncan's Test with a= 0.05. The mean flexural strength of the composites were (from highest to lowest): Clearfil AP-X (124.70 + 27.65 MPa); Filtek P-60 (108.14 + 26.39 MPa); Beautifil (92.62 + 15.80 MPa); and Solidex (48.50 + 7.78 MPa). Two-way ANOVA and Duncan's test reveal a significant difference between the mean flexural strength of these materials. Light curing followed by immersion in boiling water produced higher flexural strengths compared to light curing only. Multi-focal light oven curing produced variable results and was material dependent. However, ANOVA revealed the effect of curing methods was not significant (p=0.224). It is concluded that there is a significant difference in the flexural strengths of the four composite materials regardless of the curing methods used. It is also concluded that for each composite brand, the three curing methods produced no significant difference on the flexural strength.